Analysis of the Effect of Service Quality and Price on Customer Service Satisfaction at PT. Crieta Jakarta - Apsada Juhri; Zaenal Abidin; Mardiah Aryuni Nasution; Sudaryanti Parta (Jurnal Siber Multi Disiplin, 2026)
This research aims to determine and analyze the influence of Service Quality and Price on Customer Satisfaction at PT Crieta Jakarta from January– December 2022. Data were analyzed using quantitative analysis. Sample selection used the Solvin formula with a sample size of 33 respondents. The analytical method applied in this research is the multiple linear regression analysis method, which is fist tested throught classical tests and causal tests using E-Views software. The data used in this research are primary data from the questionnaire. Hypothesis testing was tested using the t test. The research results show that service quality and price each have a positive effect on PT. Crieta Jakarta customer satisfaction, but service quality has a significant effect while price No. significant effec. As well as service quality and price have a simultaneous influence of 68.51% on Customer Satisfaction PT Crieta Jakarta for the period January-December 2022.